Adiponectin/leptin ratio and Metabolic Syndrome in a Mexican American population - Mirza, Shaper (2011)
OBJECTIVE: Adiponectin and leptin play critical roles in the development of Metabolic Syndrome (MetS). The study was designed to assess circulating levels of adiponectin and leptin in early diagnosis of Metabolic Syndrome (MetS). METHODS: This cross-sectional study was performed on 367 participants randomly selected from a well-characterized cohort of Mexican-Americans living at the US-Mexico border. RESULTS: Significant differences in circulating levels of adiponectin and leptin were observed between males and females. The adiponectin/leptin ratio significantly correlated with MetS in this population. A receiver-operator characteristic (ROC) analysis demonstrated that adiponectin/leptin ratio is a valuable biomarker for the diagnosis of MetS CONCLUSION: Our study supported the central role of adiponectin and leptin in MetS, and demonstrated that adiponectin/leptin ratio can be used as a highly sensitive and specific biomarker for MetS.